Development of an amperometric biosensor for the detection of alcohol: a thesis presented in partial fulfilment of the requirements for the degree of Masters in Science in Biochemistry at Massey University - Large, Ruth (Massey University, 1993)
The aim of the following work was to design a biosensor for the detection of ethanol. A biosensor is an analytical device in which a biological sensing element is connected to or integrated with a physical transducing element. Amperometric enzyme biosensors utilise one or more enzymes to convert a substance which cannot be measured electrochemically to one which can be. In the case of an alcohol biosensor one of two enzymes (alcohol dehydrogenase and alcohol oxidase) can be used to convert electrochemically stable alcohol to either hydrogen peroxide or NADH which can be oxidised. In the design of an alcohol biosensor there are three major variables to consider, these are; enzyme type, electrode material, and immobilisation technique. The goal was to select optimum conditions for the formulation of the desired sensor. In the present work the electrode materials used were platinum, carbon (foil and paste) and the conducting organic salt N-methyl phenazinium.Tetracyanoquinodimethane (NMP.TCNQ). The immobilisation techniques used were; adsorption, cross-linking to a protein matrix and covalent binding. Of the biosensors produced from a selected combination or these variables each was tested by one or more of the following; cyclic voltammetry, enzyme assay, and amperometry. The most promising approach appears to be that of conjugating enzyme to haemin and allowing the conjugate to bind irreversibly to platinum via the haemin group. An electrode made with the organic salt NMP.TCNQ looked promising also but because the salt is readily oxidised it is unstable and therefore not an ideal electrode material.
Keywords: Biosensors